Effect of various packaging materials for storing ground yellow corn of hybrid C-1 variety on water and amylum content. Issue 1 (1st June 2022) - Munasik,; Nurbaety, N; Hidayat, N; Susanti, E
Abstract: This research aims to investigate the effect of various packaging materials (cotton sack and perforated plastic sack) and the storing time on ground corn quality that were assessed from water and amylum contents. The research method was experimental using Completely Randomized Design that consisted of: A (control), B (cotton sack, stored for 20 days), C (cotton sack, stored for 40 days), D (cotton sack, stored for 60 days), E (perforated plastic sack, stored for 20 days), F (perforated plastic sack, stored for 40 days), and G (perforated plastic sack, stored for 60 days). The treatments were replicated 3 times. The results showed that the longer storing time on cotton sack and perforated plastic sack resulted in higher water content and lower amylum content.